Latin America: devising public policies for Internet and information access. The case of indigenous populations - Barrantes Solano, Jurinette (2011)
The following essay reviews the public politics about information and the internet that haveexisted in Chile, Colombia, Venezuela and Costa Rica from 2000 to 2007, in order to establish inwhich  ways  have  these  countries  advanced  in  terms  of  Information  and  CommunicationTechnologies (ICTs).  An account of the policies of these countries is being made, and how it hasaffected,  in  some  cases,  the  population.  It  also  provides  a  description  of  the  environmentsurrounding indigenous communities in terms of Public Policy of Information and suggestions forimprovement.